2007
DOI: 10.1590/s1677-55382007000500010
|View full text |Cite
|
Sign up to set email alerts
|

Intracaval and intracardiac extension of Wilms' tumor: the influence of preoperative chemotherapy on surgical morbidity

Abstract: Objectives: The aim of this retrospective study is to compare surgical complications and long-term survival in children with Wilms' tumor (WT) and tumor thrombus receiving or not preoperative chemotherapy. Results: Median age was 54 months. 2/16 had cardiac failure as the first symptom. 11/16(7 IVC and 4 atrial extension) (67%) were submitted to preoperative chemotherapy with vincristine plus actinomycin D, and 5/16(1 IVC and 4 atrial) (33%) underwent initial nephrectomy and thrombus resection. So, 11 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 16 publications
4
34
0
Order By: Relevance
“…This strongly suggests that targeting transcription is a valuable anticancer approach. Moreover, additive combinations of actinomycin D with Vinca alkaloids were reported regarding their respective antiproliferative properties, suggesting the potential therapeutic benefit of combining this class of agents with triptolide (44). Furthermore, a recent publication showed that cytosine arabinoside sensitizes acute myeloid leukemia cells to low concentrations of triptolide (45).…”
Section: Discussionmentioning
confidence: 99%
“…This strongly suggests that targeting transcription is a valuable anticancer approach. Moreover, additive combinations of actinomycin D with Vinca alkaloids were reported regarding their respective antiproliferative properties, suggesting the potential therapeutic benefit of combining this class of agents with triptolide (44). Furthermore, a recent publication showed that cytosine arabinoside sensitizes acute myeloid leukemia cells to low concentrations of triptolide (45).…”
Section: Discussionmentioning
confidence: 99%
“…[7] In cases of Wilms tumor with cavo-atrial thrombus, the recommended surgical method is extraction of the primary renal and thrombus masses simultaneously in one session under cardiopulmonary bypass. [3][4][5][6][7] The overall prognosis of these patients with cavo-atrial thrombus is the same with the same histologic subtype without cavo-atrial thrombus. But as the surgical method is much more complicated, surgical morbidity and mortality is higher in patients with cavo-atrial thrombus.…”
Section: Discussionmentioning
confidence: 84%
“…In less than 1% of cases tumor thrombus may fill whole IVC and may extend into right side of the heart. [3,4] Abdullah et al reported that in 264 Wilms tumor patients 9 of them had cavo-atrial thrombus and 2 of them had right ventricular involvement. [5] In the report of Hadley et al in 10 of 406 (2.4%) Wilms tumor patients, extension of thrombus mass into the right atrium and ventricle was observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations